A Comparative Analysis of Mobile UI Testing Frameworks in Continuous Integration Environments - Costa, Gustavo; Miranda, Breno (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2023: Anais do VIII Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2023)
Mobile applications have become an integral part of modern society, driving the demand for robust and efficient mobile user interface (UI) testing frameworks. With the growing adoption of Continuous Integration (CI) practices, mobile developers seek reliable solutions that can seamlessly integrate into their CI pipelines. This paper presents a comparative analysis of popular mobile UI testing frameworks concerning their suitability for integration into CI environments. The study investigates four widely used mobile UI testing frameworks: Detox, Appium, Calabash, and Maestro. A set of evaluation criteria is established, encompassing aspects such as popularity, ease of use, and test execution speed. The results highlight the strengths and limitations of each testing framework concerning its seamless integration into CI workflows. Overall, this comparative analysis aims to assist mobile developers and organizations in making informed decisions when selecting a mobile UI testing framework for their CI processes. The findings provide insights into the strengths and weaknesses of each framework, enabling developers to align their testing strategies with CI best practices and ultimately improve the quality of their mobile applications.